(3GdJLGQI GdYGdejI Hjf GdLGJ (B94 (3hefXeI GdJLGQI GdYGdejIs - (3SejQ eMeO(B, (3YHO GdYRjRs ((3GdEScfOQjI(B:s (3ecJHI heWHYI GdETYGY GdafjI(B,s, 2001)
(3fXQI YGeI(B- (3GdEJaGbjI GdYGeI ddJLGQI aj GdSdY(B- (3GdEJaGbjI GdYGeI HGdJLGQI aj GdNOeGJ(B- (3GJaGbjI GdLhGfH GdeJUdI HGdJLGQI aj Mbhb GdedcjI GdacQjI(B- (3GdJaGge hJShjI GdefGRYGJ(B- (3hbGFY hCMOGK eG HYO JhbjY GdhKjbI GdNJGejI hbjGe efXeI GdJLGQI GdYGdejIs
Keywords: (3GdEJaGbjGJ GdJLGQjIs; (3GdJLGQI GdNGQLjIs; (3GdSdYs